Melatonin in the Biliary Tract and Liver: Health Implications - J. Reiter, Russel; A. Rosales-Corral, Sergio; C. Manchester, Lucien; Liu, Xiaoyan; Tan, Dun-Xian (Current Pharmaceutical Design, 2014)
Melatonin is a widely-produced and ubiquitously-distributed molecule with multiple critical functions in all organs and organisms. These functions are mediated by both receptor-mediated and receptor-independent actions of the indole. This survey reviews the reports documenting the presence and function of melatonin in the hepatobiliary system. The published data document the exceptionally high concentrations of melatonin in the bile; herein, we speculate on the significance of these high melatonin levels to the function of the biliary tree. Moreover, we suggest that the elevated concentrations of melatonin in the bile fluid may be a consequence of its recirculation in what is referred to as the enterohepatic circulation. The article also examines the published reports related to melatonin levels in hepatocytes, which appear to be independent of pineal-derived melatonin. In both the biliary system and liver, melatonin provides protection against free radicals in cells of these organs. This is particularly important in these organs since they are under constant assault by highly toxic agents/processes that could compromise their critical physiology. As in other tissues, melatonin provides hepatocytes and cholangiocytes with a buffer against free radicals that are persistently produced and thereby this indole protects against oxidative molecular damage and metabolic dysfunction. Melatonin achieves this protection via the diverse free radical scavenging mechanisms of it and its metabolites (known as the antioxidant cascade), due to its ability to reduce electron leakage from the respiratory complexes in the inner mitochondrial membrane (radical avoidance) and as a result of the stimulation of antioxidative enzymes.
Keywords: antioxidant